4 Pre-hospital administration of tranexamic acid in hemorrhagic trauma is associated with higher survival rates. (26th April 2019) - Garces Garces, FJ; Corral Torres, E; Lopez-Villalta Garces, JM; Silva Pereira, EJ Simones Da
Abstract : Background: Studies carried out in the hospital setting have objectivized the benefit of tranexamic acid (TXA). 1 Under the hypothesis that this is a time-dependent drug, we want to analyze the effect that a very early (on-scene) administration of the drug has over the survival of the hemorrhagic patient. Method: Cases and controls, analyzing consecutively all patients susceptible of treatment, (hemorrhagic trauma, hemodynamically unstable with evidence of bleeding, whether analytical or image-based) between 2015–2018. Cases: on-scene standard treatment administered. Controls: hospital-treated. All received TXA at varying times. Epidemiological Variables: Age, gender, lesional mechanism, severity scales: Trauma and Injury Severity Score (TRISS), Revised Trauma Score (RTS), and Injury Severity Score (ISS). Exposure variable: Early TXA administration. Dependent variable: Survival after 7 days. Inferential statistical analysis: Relationship between categorical variables by Chi-square. Multi-variate binary logistic regression (MBLR) adjusted for TRISS, RTS and ISS indices. Confidence intervals p<0.05. Results: 171 patients: 103 cases, 68 controls. Mean age: 42.05 years (SD-20.4.) 42.1% (71) deceased before 7 days. There is homogeneity in the severity indices among cases and controls: ISS; 47.5(SD:19.7) vs. 42.8 (21.5) p=0.015, RTS; 4.66(SD-2.06) vs. 4.73(SD-1.53) p=0.808 y TRISS; 63.02(SD-35.7) vs. 60.04(SD-31.6) p=0.572. After adjusting MBLR for ISS, TRISS, and RTS, survival after 7 days was higher in cases than in controls: 66.0% cases (out-of-hospital TXA administration) vs. 45.6% controls, p=0.006. Odds ratio: 2.32 (1.24–4.34.) Conclusion: Early (on-scene) TXA administration is intensely associated with an improvement in survival indices in hemorrhagic patients, which must lead to its procedural on-scene implementation. Reference: Shakur H, Roberts I, Bautista R, Caballero J, Coats T, et al . with CRASH-2 trial collaborators. Effects of tranexamic acid on death, vascular occlusive events, and blood transfusion in trauma patients with significant haemorrhage (CRASH-2): a randomised, placebo-controlled trial. Lancet 2010;376(9734):23–32. doi: 10. Conflict of interest: None. Funding: None.